Onset of Postural Instability in Parkinson’s Disease Depends on Age rather than Disease Duration - Denise Becker; Angelina Maric; Simon J. Schreiner; Fabian Büchele; Christian R. Baumann; Daniel Waldvogel (Parkinson's Disease)
Background. Postural instability and falls are considered a major factor of impaired quality of life in patients with advanced Parkinson’s disease (PD). The knowledge of the time at which postural instability occurs will help to provide the evidence required to introduce fall-prevention strategies at the right time in PD. Objective. To investigate whether postural instability of patients with different age at disease onset is associated with age or with disease duration of PD. Methods. Patients diagnosed with sporadic PD between 1991 and 2017 and postural instability (according to the International Parkinson and Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) part III, item 3.12 postural instability) were included, with strict inclusion criteria including regular follow-ups, agreement on data use, and exclusion of comorbidities affecting the free stand. Results. Applying these strict inclusion criteria, we included 106 patients. Those younger than 50 years at PD onset took significantly longer to develop postural instability (n = 23 patients, median: 18.4 years) compared with patients with later onset of PD (50–70 years, n = 66, median: 14.2 years, p<0.001; and >70 years, n = 17, median: 5.7 years, p<0.001, Kruskal-Wallis test followed by Dunn’s multiple comparisons test). There was no association between total MDS-UPDRS III (as a measure of motor symptom severity) at onset of postural instability. Conclusions. In PD, postural instability is primarily associated with the age of the patient and not with disease duration.